Surgeon techniques in non-femtosecond laser-assisted cataract surgery (TechNoFLACS) questionnaire: face and content validation - Md Mustafa, Md Muziman Syah; Mohd. Kamal, Khairidzan; Marzuki, Nazaryna; Ab. Halim, Noorhazayti; Azman, Ahmad Amiruddin; Zamzuri, Muhammad Faiz Hakim (2021)
TechNoFLACS is a set of questions related to surgeon’s techniques in performing Non-Femtosecond Laser-Assisted Cataract Surgery. This information is not commonly documented in intraoperative notes but it is essential information to study the surgeon’s techniques consistency.